PSYCHOLOGICAL FEATURES OF THE ORIGIN AND EXERCISE OF FEELING OF LONE IN YOUTH - Каряка, І.; Доценко, Л.; Каряка, O. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article describe the specificities of the emergence of the feeling of loneliness of young men as the basis for the formation of personal and professional human interaction. The main components of the emergence and manifestation of the feeling of loneliness in young people are defined: personal, emotional and behavioural. The main criteria for the emergence and manifestation of the feeling of loneliness of students are described: locus of control, anxiety and aggressiveness. The general level of expression of the feeling of solitude of young men by means of the method "Identification of the level of subjective feeling of loneliness of D. Russell and M. Ferguson, as well as the level of development of the personal component of the emergence and manifestation of the feeling of loneliness of students by means of methods and "Locus of control" J. Rotter, the diagnosis of the level of development of the emotional component of the emergence and manifestation of the feeling of solitude of young men was carried out behind the school "anxiety" of the methodology "Self-assessment of mental states" Eisenka, the level of formation of Povedko the same component of the occurrence and manifestation of loneliness of persons of youthful age was studied on the scale "anxiety" of the methodology "Self-assessment of mental states" Eis. As a result of the pilot study, it was recognized that the emergence of a feeling of loneliness in young men has a certain hierarchical structure of their origin and manifestation, where locus control is the primary link of this phenomenon. This personality characteristic of young men determines the degree of anxiety, which in turn determines the manifestation of aggressiveness of young people. It is this sequence, the factors identified by us, that acts as the law of the emergence of anxiety of young men. Based on the results of the pilot study carried out, we provided practical recommendations to young men to reduce the level of occurrence and manifestation of a feeling of loneliness among young people.